2011
DOI: 10.1002/mop.26526
|View full text |Cite
|
Sign up to set email alerts
|

An efficient second‐order model reduction enhanced by H‐LU for the finite element method full‐wave electromagnetic simulations

Abstract: In this work, a UWB BPF based on the uniform MMR using a pair of MMRs is proposed. All three resonant frequencies within the UWB BPF are reassigned and the spacing g between the two parallel-coupled MMRs is properly regulated, a UWB filter with high performances is obtained. Measured results show high performances with insertion loss lower than 2 dB (from 3.1 to 7.5 GHz lower than 0.5 dB) and return loss higher than 10 dB (from 3.2 to 8.9 GHz higher than 15 dB) as well as group delay variation less than 0.18 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It is found that (6) is linear with respect to the frequency s . As a result, the SOAR algorithm in [3, 4] can be applied to obtain the projection matrix Q of q orthogonal vectors. If we let x=Qx^, then (6) can be written as ][QTZ0+QTZ1)(s0+s+QTZ2s0+s2Qx^)(s0+s=QTbthen a reduced model can be obtained after projections ][Z^0+Z^1)(s0+s+Z^2s0+s2bold-italicxfalse^)(s0+s=bold-italicbfalse^where bold-italicZfalse^0=QTZ0Q, bold-italicZfa...…”
Section: Reduced Model Of Mom With Soarmentioning
confidence: 99%
See 3 more Smart Citations
“…It is found that (6) is linear with respect to the frequency s . As a result, the SOAR algorithm in [3, 4] can be applied to obtain the projection matrix Q of q orthogonal vectors. If we let x=Qx^, then (6) can be written as ][QTZ0+QTZ1)(s0+s+QTZ2s0+s2Qx^)(s0+s=QTbthen a reduced model can be obtained after projections ][Z^0+Z^1)(s0+s+Z^2s0+s2bold-italicxfalse^)(s0+s=bold-italicbfalse^where bold-italicZfalse^0=QTZ0Q, bold-italicZfa...…”
Section: Reduced Model Of Mom With Soarmentioning
confidence: 99%
“…However, when the matrix equation represents quadratic dependence with respect to frequency, the standard Arnoldi process cannot be employed directly. A second‐order Arnoldi (SOAR) [3] process is proposed for the quadratic systems resulting from the FEM [4]. For the microstrip circuits, the method of moments (MoMs) with the layered media Green's function, only need to discretise the surface of the conductor as unknowns.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations